Variation in performance of elite cyclists from race to race - Paton, C. D.; Hopkins, W. G. (European Journal of Sport Science, 2006)
The race-to-race variation in performance of a top athlete determines the smallest change in performance affecting the athlete's chances of winning. We report here the typical variation in competition times of elite cyclists in various race series. Repeated-measures analysis of log-transformed official race times provided the typical variation in a cyclist's performance as a coefficient of variation. The typical variation of a top cyclist (and its 95% likely limits) was 0.4% (0.3-0.5%) in World Cup road races, 0.7% (0.7-0.8%) in Tour de France road races, 1.2% (0.8-2.2%) in the Kilo, 1.3% (0.9-2.4%) in road time trials, 1.7% (1.2-2.6%) in Tour de France time trials, and 2.4% (2.1-2.8%) in World Cup mountain biking. Cyclist interdependence arising from team tactics and pack riding probably accounts for the lower variability in performance of cyclists in road races and precludes estimation of the smallest worthwhile change in performance time for cyclists in these events. The substantial differences in variability between the remaining events, where riders act independently of each other, arise from various event-specific aspects. For these events the smallest worthwhile changes in performance time (~0.5×typical variation) are ~0.5% in the Kilo, ~0.6% in road time trials, and ~1.2% in mountain-bike races.